Ultimate Certified Kubernetes Administrator (CKA) Certification Guide: Become CKA Certified with Ease by Mastering Cluster Management and Orchestration with Kubernetes (English Edition) - Gheware, Rajesh Vishnupant (Orange Education Pvt Ltd, 2025)
Embark on a journey from beginner to pro with this CKA Certification Guide. Seamlessly blending theory with hands-on practice, this indispensable Kubernetes companion provides clear explanations and real-world scenarios to guide you to success in Kubernetes administration. The book starts by giving a solid understanding of Kubernetes platform and how to confidently set up your clusters with step-by-step instructions. You will dive into Workload Objects to master crucial concepts, then explore Service and Ingress for a deep understanding of networking. Next, it moves to deploy and scale applications, ensuring you're ready for any workload. This book offers the tools needed to design, deploy, and maintain efficient, scalable, and resilient applications in Kubernetes environments. It covers essential topics such as Pods, Deployments, and StatefulSets, along with providing insights into Kubernetes architecture and operations. The advanced section of the book focuses on enhancing your skills with chapters on security and troubleshooting, ensuring you can maintain your clusters effectively and managing microservices with precision. The final section of the book covers focused content and practice exercises to prepare you to ace the CKA certification exam.